2021
DOI: 10.3389/fcell.2021.708513
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells With Cancer-Associated Fibroblast-Like Phenotype Stimulate SDF-1/CXCR4 Axis to Enhance the Growth and Invasion of B-Cell Acute Lymphoblastic Leukemia Cells Through Cell-to-Cell Communication

Abstract: Background: Bone marrow mesenchymal stem cells (BM-MSCs) are the stromal cells in the leukemia microenvironment, and can obtain cancer-associated fibroblast (CAF)-like phenotype under certain conditions to further promote leukemia progression. However, the mechanism of MSCs with CAF-like phenotype interacting with leukemia cells in B-cell acute lymphoblastic leukemia (B-ALL) and promoting the progression of B-ALL remains unclear.Methods: Mesenchymal stem cells with CAF-like phenotype were obtained by treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Another example of how the cross‐talk between MSCs and leukaemia cells can serve as a target for novel therapy was reported with the CXCR‐4 inhibitor AMD300. Treatment with AMD300 blocked the leukaemia growth and migration of leukaemic cells enhanced by MSCs 150 …”
Section: Mesenchymal Cells' Significance In Haematological Malignanciesmentioning
confidence: 95%
See 2 more Smart Citations
“…Another example of how the cross‐talk between MSCs and leukaemia cells can serve as a target for novel therapy was reported with the CXCR‐4 inhibitor AMD300. Treatment with AMD300 blocked the leukaemia growth and migration of leukaemic cells enhanced by MSCs 150 …”
Section: Mesenchymal Cells' Significance In Haematological Malignanciesmentioning
confidence: 95%
“…Treatment with AMD300 blocked the leukaemia growth and migration of leukaemic cells enhanced by MSCs. 150 Finally, MSCs have been shown to modulate AML cell proliferation by the release of miRNA in small EVs. This has been shown to affect key regulatory pathways in leukaemia including PI3K/AKT/mTOR, affecting both proliferation and resistance to chemotherapy.…”
Section: The Role Of Mscs In Leukemogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Other candidate cell types hypothesised as precursors of CAFs and factors stimulating their formation [59][60][61][62][63][64][65] are included in Table 1. Members of the TGF-β family seem to be the most frequently discussed in this context as inducers of the transition of precursor cells to myofibroblasts [66].…”
Section: Origin Of Cafsmentioning
confidence: 99%
“…Then, Pan et al. ( 145 , 146 ) found that TGF-β is a key factor for BM MSCs to obtain a CAF-like phenotype in a B-ALL microenvironment, which may interact with ALL cells through an SDF1-CXCR4 signaling axis to promote the progression of B-ALL. Using single-cell sequencing, Baryawno et al.…”
Section: Cafs In the Bmm Of Leukemiamentioning
confidence: 99%